Empowering the Educators: Understanding Professional Challenges and Resilience among Nepali Mathematics Teachers - Dahal, Prem Prasad (Educational Journal, 2025)
Mathematics teachers in Nepal face complex professional problems in the context of limited resources, the variability in learner readiness, technological gaps and rising expectations in terms of teaching quality. This research seeks to understand major problems that secondary-level mathematics teachers are facing in their field professionally and classroom related and also to investigate the actions and coping mechanisms they use in order to remain effective in their work. Adopting a qualitative descriptive design, the study collected data from five teachers of mathematics at the secondary level in different districts using an open-ended online questionnaire. The responses were thematically analyzed by an approach of inductive coding. The results showed four major themes, namely: (1) pedagogical and classroom problems, which were weak foundational knowledge among students, irregular attendance, large class sizes, and low integration of ICT; (2) institutional and policy-related constraints, which included lack of school management support, lack of adequate teaching materials, and curriculum pressure; (3) emotional and motivational struggles, which manifested in loss of confidence, high stress levels, and undervaluation; and (4) strategies to build resilience, which included constant self-study, peer collaboration, use of local teaching aids, student counselling, and positive teacher-student relationships. The study concludes that strengthening teacher resilience in Nepal requires concerted efforts of policy makers, school leaders and training institutions in ensuring that teachers have access to regular training, ICT facilities, mentoring systems and supportive policies which empower teachers professionally.